Educational policies for disabled people: an analysis based on national and international documents (Research, Society and Development, 2020)
This work is the result of a research that aims to study the process of inclusion of disabled people in postgraduate programs at the Federal University of Paraiba through access and permanence in these programs. More specifically, the article aims to analyze the main international and national documents, conferences, conventions and declarations that influenced the construction of education policy aimed at promoting the right to education of disabled people. It is a qualitative study supported by bibliographic and documentary research, which seeks to point out the importance of these documents for the promotion and realization of the right to education of disabled people.